Osteogenesis imperfecta and clubfoot—a rare combination: Case report and review of the literature. Issue 31 (August 2016) - Persiani, Pietro; Ranaldi, Filippo Maria; Martini, Lorena; Zambrano, Anna; Celli, Mauro; D'Eufemia, Patrizia; Villani, Ciro
Abstract: Background: Osteogenesis imperfecta (OI) is a rare congenital genetic osteodystrophy, which has a prevalence of 1:20, 000. OI is caused by the mutation of the COL1A1/COL1A2 genes, leading to a deficit of quality and/or quantity in the synthesis of procollagen-α type 1. Seven different forms of diverse clinical entity have been classified by Sillence and Glorieux, although, recently, up to 11 forms characterized by different genetic mutations have been recognized. Patients with OI suffer from extreme bone fragility and osteoporosis, which often predisposes them to frequent fractures. This paper presents the case of a child with OI type IV who, at birth, was also diagnosed with a severe clubfoot (congenital talipes equinovarus) grade III. Patient's mother also suffers from OI type IV. Methods: The treatment was started by placing femoro-podalic corrective casts, according to the Ponseti method, but some unexpected problems occurred during this treatment. When the patient was 3 months of age, we decided to correct the clubfoot before the time limit planned, performing a bilateral posteromedial surgical release. Results: Three weeks after surgery the casts were removed and replaced with bilateral Spica cast-like braces. On the 6th postoperative week, the patient began wearing Bebax corrective shoes, after 1 year ambidextrous orthopedic shoes. Now, he is 2 years old and has started to walk properly without any orthesis. Conclusion: In the presence of an orthopedic pathology associated with OI, it is recommended to manage the patient according to the underlying pathology, always considering the bone fragility associated with OI. The final surgical treatment to correct the clubfoot can be done earlier, if necessary. In our opinion, this uncommon association between OI and clubfoot is non-syndromic. This means that the two congenital diseases are not necessarily included in a singular uncommon genetic syndrome, but the clubfoot was caused by multifactorial causes, especially by both the mother's bisphosphonate drug therapy and the amniocentesis performed during her pregnancy to drain polyhydramnios. In our analysis, those environmental factors could have interacted with an already altered genetic substratum, contributing to develop this rare combination of congenital disorders.